Journalists at Risk: News Media Perspectives - Robie, D; Edwards, B; Field, M; Bennett, C; Stephenson, J (Pacific Media Centre, AUT University, 2010)
On May 22, 2009, Massey University’s Wellington campus hosted many speakers addressing the conference on war reporting jointly organised by the International Committee of the Red Cross. Media speakers included Television New Zealand’s Sunday programme reporter Cameron Bennett; Radio NZ political editor Brent Edwards; Fairfax NZ reporter Michael Field; Fairfax Media editorial development manager Clive Lind; Pacific Media Centre director and AUT University associate professor Dr David Robie; freelance foreign correspondent Jon Stephenson; and Radio NZ International news editor Walter Zweifel. Commentaries, in some cases transcribed from recordings of proceedings, have been abridged. This transcript was compiled by Massey journalism programme lecturer Alan Samson.
Keywords: Conflict reporting; Foreign correspondent; Global reporting; Humanitarian organisations; Insurgencies, post-traumatic stress disorder; Journalism training; War reporting; War correspondent